Multiphase flow : theory and applications. (WIT Press, 2018)
The selected papers contained in this book present the latest research in one of the most challenging, yet most universally applicable areas of technology. Multiphase flows are found in all areas of technology and the range of related problems of interest is vast, including many areas of science and engineering.